Association of Urinary Incontinence with Instrumental Vaginal Delivery in Females Presenting at Term in Labor - Alqai, Sodat; Naz, Sobia; Munir, Shamila Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To find the association of urinary incontinence with instrumental vaginal delivery among women presenting at term in labor at a tertiary care hospital. Material and methods: Between August 2020 to February 2021 total 180 (90 patients in un-exposed, 90 patients in exposed group) pregnant women delivering at term with either instrumental vaginal delivery or spontaneous vaginal delivery having age 20-40 years, gestation age 37-41 weeks were selected from Obstetrics and Gynecology Department, Sir Ganga Ram Hospital, Lahore. Association of urinary incontinence with instrumental vaginal delivery among women presenting at term in labor were studied. Results: Mean age of patients was 30.17 ± 5.87 years with age range 20-40 years. In un-exposed group, urinary incontinence was develop in 6 (6.67%) patients and in exposed group, urinary incontinence was develop in 21 (23.33%) patients. Difference of urinary incontinence between the both groups was statistically significant (P=0.004. Findings also showed that there is 3.5 times more risk of development of urinary incontinence in exposed group as compared to un-exposed group. (RR = 3.5) Conclusion: This study concluded that the frequency of urinary incontinence is higher after instrumental vaginal delivery among women presenting at term in labor as compared to spontaneous vaginal delivery.